2015
DOI: 10.1097/md.0000000000001279
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adenosine in Patients With Acute Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: Whether adenosine offers cardioprotective effects when used as an adjunctive therapy for patients with acute myocardial infarction (AMI) undergoing primary percutaneous coronary intervention (PCI) remains controversial.To evaluate, via meta-analysis, the efficacy of adenosine in patients with AMI undergoing PCI.Randomized controlled trials (RCTs) published in Medline, Embase, and the Cochrane Central Register of Controlled Trials.RCTs of patients with AMI undergoing primary PCI, comparing adenosine treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
1
20
0
1
Order By: Relevance
“…These combined effects are expected to help promote myocardial recovery. Other possible approaches that have been evaluated to reduce reperfusion injury following PCI in patients with STEMI have included ischemic conditioning [48,49] and adenosine [50,51]: the results of these studies varied in terms of myocardial protection and survival benefits.…”
Section: Discussionmentioning
confidence: 99%
“…These combined effects are expected to help promote myocardial recovery. Other possible approaches that have been evaluated to reduce reperfusion injury following PCI in patients with STEMI have included ischemic conditioning [48,49] and adenosine [50,51]: the results of these studies varied in terms of myocardial protection and survival benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Tres metaanálisis recientes permiten concluir que la adenosina intracoronaria utilizada en pacientes con SCAcST tratados con ATC primaria se asocia con menor incidencia de flujo TIMI <3 y mayor frecuencia de renivelación del segmento ST (28)(29)(30) . El metaanálisis de red de Niu y colaboradores evaluó el efecto de siete agentes farmacológicos de uso intracoronario (adenosina, anisodamina, diltiazem, nicorandil, nitroprusiato, urapidil y verapamil) sobre el NR en pacientes con SCAcST tratados con ATC primaria.…”
Section: Discussionunclassified
“…No -reflow is a complication of PCI, where the flow in a coronary vessel stops despite effective revascularization. Myocardial infarction complicated by no -reflow is difficult to treat and is associated with a worse prognosis for the patient [63]. In their papers, these authors stressed that the shortest possible time before restoration of coronary artery patency was the factor that determined whether the aforementioned benefits were achieved or not.…”
Section: Adenosine As An Adjunct To Reperfusion Therapy In Myocardialmentioning
confidence: 99%
“…The results of 3 meta -analyses published in 2015-2016 [55,63,71] agreed that adenosine improved myocardial perfusion and prevented no -reflow, although Bulluck et al [71] indicated that this effect was observed following intracoronary administration rather than intravenous infusion. Moreover, adenosine decreased the prevalence of heart failure and improved LVEF [63]. Nevertheless, no clinical benefits were observed, such as a reduced risk of death [55,63] or subsequent infarction [63].…”
Section: Adenosine As An Adjunct To Reperfusion Therapy In Myocardialmentioning
confidence: 99%
See 1 more Smart Citation